Dyadic Universal functions and simultaneous near-field/far-field regularization of elasto-dynamic dyadic Green's functions for 3D mass-loading analysis in micro-acoustic devices - Baghai-Wadji, A. R. (2015 IEEE International Ultrasonics Symposium (IUS), 2015)
Assuming an infinite-domain isotropic elastic medium, and a vector-force Dirac delta function fδ(x - x', y - y', z - z') excitation, dyadic Green's functions (DGFs) for three dimensional massloading analysis have been constructed in spectral domain. The construction procedure follows an earlier scheme by utilizing the diagonalization of the governing equations subject to radiation conditions. Consecutively, DGFs have been employed for obtaining the associated stress distributions. It is shown that the latter distributions induce novel problem-specific expressions for parametrized "smeared out" Dirac delta function δ η (x - x',y - y'). Using δ η (x - x', y - y') exponentially-regularized DGFs have been obtained. The notion of Univeral functions, also introduced earlier, has been utilized, showing that, in addition to the exponential regularization, the DGFs can be regularized algebraically.